Contribution of the Agricultural Sector and Manufacturing to the Regional Original Income of Trenggalek Regency - Rima Restiani,; Widyastuti, Dyah Erni (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
Countries in the world certainly need economic development, one of which is Indonesia. The Indonesian Government needs to improve the people's standard of living and welfare. Regional Original Income can be used to find out how big the contribution of the economic sector is by comparing the Gross Regional Domestic Product (GRDP) generated from each sector. This study aims at describing the contribution of the GRDP of the agricultural and the manufacturing sector to the ROI of Trenggalek Regency. This study uses quantitative methods. The data used is secondary data in the form of time series from 2012 to 2018. The data analysis used is descriptive to determine the percentage of contribution. The results showed that the average contribution of the agricultural sector and the manufacturing industry in 2012-2018 was 2.988% and 1.403%, respectively, so it is concluded that their contribution was far lower from the ROI. Based on the results of research, the increase in ROI is a lot higher than GRDP from 2012 to 2018, and therefore the percentage of contribution is insignificant, and the two sectors have no effect on ROI in Trenggalek Regency.